Hubungan Personal Hygiene Dengan Kejadian Diare Pada Santri Di Kota Tangerang Selatan - Nabilah Nur Haenisa; Istianah Surury (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Diarrhea is a disease caused by infection with microorganisms in the environment, its transmission is related to the mouth and its spread is almost all over the world. South Tangerang City has determined that children aged 5-14 years are the third most common causes of diarrhea, with an incidence rate of 2.6% and a prevalence period of 4.7%. This study was conducted to determine the relationship between personal hygiene with the incidence of diarrhea in students at the Ummul Quro Islamic Boarding School in 2021. This research is quantitative research with an analytical observational approach with a cross-sectional study design. Data collection was carried out primarily using a questionnaire with a total sample of 133 respondents who were taken using a total sampling technique. The results obtained as many as 77 respondents (57.9%) experienced diarrhea from the last month. The results of the bivariate test with the Chi-Square test showed that age (p-value=1,000), gender (p-value=0.691), snack habits (p-value=0.801) did not have a significant relationship. While the personal hygiene variable (p-value=0.006) had a significant relationship with the incidence of diarrhea. In this study, the personal hygiene variable had a significant relationship with the incidence of diarrhea. Islamic boarding schools are required to provide education to santri related to good personal hygiene to prevent diarrhea and to support all facilities and infrastructure that support personal hygiene.